KONSUMSI PANGAN, PENYAKIT INFEKSI, DAN STATUS GIZI ANAK BALITA PASCA PERAWATAN GIZI BURUK - Karlina Nurcahyo; Dodik Briawan (Jurnal Gizi dan Pangan, 2010)
The research objective was to determine food consumption, infectious diseases, and nutritional status of children under-five years old after the treatment of severe malnutrition at Puskesmas. The cross-sectional study design was conducted in four sub-districs in Bogor.  The number of 27 children was selected purposively out of 44 patients at the Puskesmas. The results showed that 88.9% and 77.8% of children consumed less than 70% RDA of energy and protein. In the last three months, the most children suffered from diarrhoea (55.6%) and ARI (59.3%). There were 81.5% of children still in severe malnutrition and only 18.5% of them shifted to the moderate malnutrition.